Heat transfer in a square cavity filled by nanofluid with sinusoidal wavy walls at different wavelengths and amplitudes - Mohammad Sharif Zarei; Amir Taghavi Khalil Abad; Maboud Hekmatifar; Davood Toghraie (Case Studies in Thermal Engineering, 2022)
This study's main purpose is to investigate the wavy wall effect with a sinusoidal function on two-dimensional natural convection in a cavity with Cu-Water nanofluid. The SIMPLE algorithm is used to solve the FVM discretized governing Equations of velocity field and heat transfer. The effect of wall wavelength, amplitude, and volume fraction (VF) of nanoparticles, is investigated at a Rayleigh number of 10000 to find the optimal heat transfer mode. The amplitude varied from 0 to 0.15, the wavelength from 0.25 to 1, and the concentration of nanoparticles is changed from 0 to 0.04. The effect of all three parameters is determined separately by statistical analysis using the signal-to-noise ratio. According to the results, the most important parameter that can affect heat transfer is VF. As the VF increases from 0 to 0.04, the average Nusselt number (Num) increases by about 2.5 times. For example, at amplitude A = 0.05, wavelength B = 0.25, with increasing VF from 0 to 0.04, the null number increases from 35.30086 to 90.4793. In contrast, wall wavelength has the least effect on it. Three steps of −1, 0, and +1 are defined for further investigation of heat transfer. The wavy wall's Num increases with increasing VF and wavelength from step −1 to +1. The surface heat transfer coefficient also shows an increasing trend.